Managing athlete’s foot - Nkatoko Freddy Makola; Nicholus Malesela Magongwa; Boikgantsho Matsaung; Gustav Schellack; Natalie Schellack (South African Family Practice)
This article is aimed at providing a succinct overview of the condition tinea pedis, commonly referred to as athlete’s foot. Tinea pedis is a very common fungal infection that affects a significantly large number of people globally. The presentation of tinea pedis can vary based on the different clinical forms of the condition. The symptoms of tinea pedis may range from asymptomatic, to mild-to-severe forms of pain, itchiness, difficulty walking and other debilitating symptoms. There is a range of precautionary measures available to prevent infection, and both oral and topical drugs can be used for treating tinea pedis. This article briefly highlights what athlete’s foot is, the different causes and how they present, the prevalence of the condition, the variety of diagnostic methods available, and the pharmacological and non-pharmacological management of the condition.